Wisconsinan Inter-Lobal Stratigraphy in Three Quarries Near Woodstock, Ontario - Krzyszkowski, Dariusz; Karrow, P. (Géographie physique et Quaternaire, 2001)
AbstractThe Huron-Erie interlobate zone passes near Woodstock, Ontario. Three large limestone quarries (Zorra, Beachville West, Beachville East) provide exposures up to 30 m high of the drift stratigraphy. Grain size, matrix carbonate, color, structure, fabric, lithology, and sequence, along with continuous tracing of contacts and facies changes, allowed recognition of ten tills and related water-laid sediments correlated with the known stratigraphy in surrounding areas.Four major glacial events are recognized, three of Late Wisconsinan age. Three tongues of red, Erie lobe Canning Till (unknown age) are over-lain by a Nissouri Stadial (22-17 ka) Catfish Creek Drift complex (two till tongues, regional southwest ice flow). Similar, apparently correlative, glacial and non-glacial sediment sequences within Catfish Creek Drift at Zorra and Beachville West (Centreville Member) suggest a northwest-southeast-trending ice margin. Overlying this are Erie Interstadial (16 ka) glaciolacustrine sediments (Rayside beds), Port Bruce Stadial (15-14 ka) Erie lobe Port Stanley Till, glaciolacustrine Zorra beds, and final Port Bruce Stadial Huron lobe Tavistock Till (three tongues), and deglacial out-wash (Dunn's Corner gravels). Repeated glaciolacustrine sedimentation between tills may relate to glacioisostatically reduced gradients and nearby ice lobe margins. There is little evidence of Catfish Creek interlobate conditions and only independent lobal glacial advances later.